Industrial Democracy - McCaffrey, Gordon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1972)
The purpose of this paper is to examine the concept of participation by workers in jobs and management and to come to some conclusions as to the role of industrial democracy, in Us various definitions, present and future, in Canadan Industrial Relations.